Energy modeling and visualization analysis method of drilling processes in the manufacturing industry. (1st August 2021) - Jia, Shun; Cai, Wei; Liu, Conghu; Zhang, Zhongwei; Bai, Shuowei; Wang, Qiuyan; Li, Shuoshuo; Hu, Luoke
Abstract: Energy modeling and visualization of machining have been recognized as effective and powerful ways to explore energy-saving potential and to improve energy efficiency. However, energy modeling and visualization of the drilling process have not been investigated adequately. To address this challenge, sub-power models-based energy modeling and multi-angle energy visualization analysis methods of drilling process were proposed in this study. More specifically, three tasks were carried out: (1) detailed sub-power models of drilling were established; (2) sub-power models-based energy modeling method of drilling was proposed; (3) based on the detailed sub-power models and energy data, multi-angle energy visualization analysis was conducted. Application of the proposed drilling energy model in common drilling processes indicated that its average prediction accuracy of the proposed drilling energy model was 96.2%. The results also showed that 7417.8 J energy saving and 12.6% energy efficiency improvement were achieved with the visualization analysis. The proposed method contributed to energy-saving activities for the drilling process, including providing high accuracy energy model, analyzing energy saving potential and improving energy efficiency. We believe that the outcomes of this research can help engineers and managers to better understand and manage the energy characteristics of drilling. Highlights: Proposing a new, sub-power-based energy modeling method of drilling. Average prediction accuracy of drilling energy is improved to 96.2%. A novel multi-angle energy visualization analysis method is proposed. 7417.8 J energy saving potential is identified by energy visualization analyzing. Energy efficiency is improved by 12.6% through implementing the proposed method.